Actual experience of the training effect of Baduanjin on patients with hemiplegic limb dysfunctions after cerebral infarction: A qualitative study. Issue 2 (25th September 2022) - Liao, Yan‐tan; Zheng, Qing‐Xiang; Huang, Ping‐ping; Xie, Qiu‐lin; Wang, Guan‐dong; Lai, Yu‐ting; Jiang, Xin‐yong; Ge, Li
Abstract: Aim: To explore the actual experience of training effect of Baduanjin on patients with hemiplegic limb dysfunctions after cerebral infarction through semistructured interviews and promote Baduanjin training application in clinical and community settings. Design: This qualitative study was conducted using the conventional content analysis approach. Methods: Twenty‐five patients with hemiplegic limb dysfunctions after cerebral infarction were recruited as participants by applying purposive sampling method between September 2017–December 2020 in the physical therapy department of a rehabilitation hospital affiliated with Fujian University of Traditional Chinese Medicine in China. Semistructured interviews were conducted after patients participated in Baduanjin training for 6 weeks. Data were analysed using qualitative content analysis method of Graneheim and Lundman. Results: Three major themes were identified after analysis, namely improving functions of hemiplegic limbs, improving the condition of the entire body and the feelings of practice. The participants indicated that Baduanjin could improve the limb functions and general conditions of hemiplegic patients. Their experience in practicing Baduanjin was generally positive, and they were willing to continue practicing.